Rhythmic finger tapping reveals cerebellar dysfunction in essential tremor. Issue 4 (April 2015) - Buijink, A.W.G.; Broersma, M.; van der Stouwe, A.M.M.; van Wingen, G.A.; Groot, P.F.C.; Speelman, J.D.; Maurits, N.M.; van Rootselaar, A.F.
Abstract: Introduction: Cerebellar circuits are hypothesized to play a central role in the pathogenesis of essential tremor. Rhythmic finger tapping is known to strongly engage the cerebellar motor circuitry. We characterize cerebellar and, more specifically, dentate nucleus function, and neural correlates of cerebellar output in essential tremor during rhythmic finger tapping employing functional MRI. Methods: Thirty-one propranolol-sensitive essential tremor patients with upper limb tremor and 29 healthy controls were measured. T2*-weighted EPI sequences were acquired. The task consisted of alternating rest and finger tapping blocks. A whole-brain and region-of-interest analysis was performed, the latter focusing on the cerebellar cortex, dentate nucleus and inferior olive nucleus. Activations were also related to tremor severity. Results: In patients, dentate activation correlated positively with tremor severity as measured by the tremor rating scale part A. Patients had reduced activation in widespread cerebellar cortical regions, and additionally in the inferior olive nucleus, and parietal and frontal cortex, compared to controls. Conclusion: The increase in dentate activation with tremor severity supports involvement of the dentate nucleus in essential tremor. Cortical and cerebellar changes during a motor timing task in essential tremor might point to widespread changes in cerebellar output in essential tremor. Highlights: A large homogeneous sample of propranolol-sensitive essential tremor patients is included. Tremor severity correlates with dentate nucleus activation during an fMRI motor timing task. Decreased activity of the entire olivocerebellar system is observed in essential tremor patients compared to controls. Cerebellar cortical dysfunction might lead to altered dentate and inferior olive nucleus activation in essential tremor.